Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To write the function represented by the equation [tex]\( 9x + 3y = 12 \)[/tex] in function notation with [tex]\( x \)[/tex] as the independent variable, we need to isolate [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex].
1. Start with the original equation:
[tex]\[ 9x + 3y = 12 \][/tex]
2. Subtract [tex]\( 9x \)[/tex] from both sides to isolate the [tex]\( 3y \)[/tex] term:
[tex]\[ 3y = 12 - 9x \][/tex]
3. Divide both sides by [tex]\( 3 \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{12 - 9x}{3} \][/tex]
4. Simplify the right-hand side:
[tex]\[ y = \frac{12}{3} - \frac{9x}{3} \][/tex]
[tex]\[ y = 4 - 3x \][/tex]
Now that we have [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex], we can rewrite the equation as a function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = -3x + 4 \][/tex]
Therefore, the function in notation form is:
[tex]\[ f(x) = -3x + 4 \][/tex]
Among the given choices, the correct function notation is:
[tex]\[ f(x) = -3x + 4 \][/tex]
1. Start with the original equation:
[tex]\[ 9x + 3y = 12 \][/tex]
2. Subtract [tex]\( 9x \)[/tex] from both sides to isolate the [tex]\( 3y \)[/tex] term:
[tex]\[ 3y = 12 - 9x \][/tex]
3. Divide both sides by [tex]\( 3 \)[/tex] to solve for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{12 - 9x}{3} \][/tex]
4. Simplify the right-hand side:
[tex]\[ y = \frac{12}{3} - \frac{9x}{3} \][/tex]
[tex]\[ y = 4 - 3x \][/tex]
Now that we have [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex], we can rewrite the equation as a function [tex]\( f(x) \)[/tex]:
[tex]\[ f(x) = -3x + 4 \][/tex]
Therefore, the function in notation form is:
[tex]\[ f(x) = -3x + 4 \][/tex]
Among the given choices, the correct function notation is:
[tex]\[ f(x) = -3x + 4 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.